Evaluation of investment preference with phantasy, emotional intelligence, confidence, trust, financial literacy and risk preference - Aren, Selim; Nayman Hamamci, Hatice (EMERALD GROUP PUBLISHING LTD, 2023)
Purpose There is strong excitement during Ponzi schemes and financial bubble periods. This emotion causes investors to turn to unknown and new investment instruments. This study, the factors that made unknown and new investment instruments preferable to known and experienced investment instruments were investigated. Design/methodology/approach It was taken into account unconscious like phantasy, emotional like emotional intelligence, both affective and cognitive like financial literacy and subjective beliefs like trust and overconfidence. In addition, risk preferences were measured with four different risk variables. In this context, data were collected by online survey method between November 2020 and May 2021 with convenience sampling. First, the data were collected from 832 participants in the pilot study. Additional data were also collected using convenience sampling and online surveys, and a total of 1,692 participants were obtained. Data were analyzed using Statistical Package for the Social Sciences (SPSS) 25 and AMOS 24. Findings As a result of the analyses made, the variables that lead investors to choose unknown and new investment instruments were determined as risky investment intention, phantasy, risk taking/risk avoidance, confidence, risk tolerance and subjective financial literacy. Trust and risk perception have a very weak effect on preferences. However, no effect of emotional intelligence and objective financial literacy was detected. In addition, a moderately positive and significant relationship was found between objective and subjective financial literacy. Subjective financial literacy was found to have a strong and significant relationship with emotional intelligence, confidence, trust, risky investment intention and phantasy. Originality/value This study investigates the factors underlying individuals' investment preferences from a broad perspective. We think that this study is unique in this structure and wide variables. We believe that the findings obtained in this manner are unique to both academics and practitioners. We also believe that the findings of the study will make an important contribution to understanding participation behavior in various Ponzi schemes and financial bubbles.
Keywords: Phantasy; Emotional intelligence; Financial literacy; Confidence; Trust; Risk; Investment preference; GENDER-DIFFERENCES; COPING STRATEGIES; TAKING BEHAVIOR; PERCEIVED RISK; UNIVERSITY-STUDENTS; DECISION-MAKING; SELF-CONFIDENCE; HERD BEHAVIOR; PERCEPTION; TOLERANCE; Computer Science